2006
DOI: 10.1037/1040-3590.18.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Separating optimism and pessimism: A robust psychometric analysis of the Revised Life Orientation Test (LOT-R).

Abstract: The internal structure of the revised Life Orientation Test (LOT-R, German version; M. F. Scheier, C. S. Carver, & M. W. Bridges, 1994) was analyzed in a sample of 46,133 participants who ranged in age from 18 years to 103 years. Confirmatory factor analysis showed that dispositional optimism, as measured by the LOT-R, is bidimensional, consisting of an Optimism and a Pessimism factor. Consistent with previous results, there were small to moderate negative correlations between Optimism and Pessimism, but the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
246
2
26

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(291 citation statements)
references
References 25 publications
17
246
2
26
Order By: Relevance
“…Factorial analysis in different studies usually indicate two distinct elements, one composed by items written in the positive direction and another in the negative direction (Herzberg, Glaesmer, & Hoyer, 2006;Marshall, Wortman, Kusulas, Herving, & Vickers, 1992;Scheier & Carver, 1985;Vautier, & Raufaste, 2006). The identification of these two factors may be understood as a methodological problem; however, it may be a conceptual issue.…”
Section: Discussionmentioning
confidence: 99%
“…Factorial analysis in different studies usually indicate two distinct elements, one composed by items written in the positive direction and another in the negative direction (Herzberg, Glaesmer, & Hoyer, 2006;Marshall, Wortman, Kusulas, Herving, & Vickers, 1992;Scheier & Carver, 1985;Vautier, & Raufaste, 2006). The identification of these two factors may be understood as a methodological problem; however, it may be a conceptual issue.…”
Section: Discussionmentioning
confidence: 99%
“…Three items measure optimism (eg, 'Overall, I expect more good things to happen to me than bad'), three items measure pessimism (eg, 'I rarely count on good things happening to me'), and four items are fillers (eg, 'It's important for me to keep busy'). The LOT-R demonstrated acceptable internal consistency for optimism (α = 0.71) and moderate internal consistency of pessimism (α = 0.68), in a primary care sample (Herzberg et al, 2006;Hirsch et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Vautier, Raufaste, and Cariou, (2003) with a French sample using confirmatory factor analysis, discussed Lai et al (1998) results and concluded that there is no empirical necessity for hypothesizing that the dispositional optimism construct must be split into optimism and pessimism, but that the question of the definition of the basic psychological dimensions underlying the data is still wide open. With a large German sample, Herzberg et al (2006) compared the one and two factor hypothesis and found a good fit for the two factors solution and a non fit of the data for the one factor solution, and "recommend that future research use separate measures of optimism and pessimism with all age groups, and we advise researchers to use caution when interpreting results of empirical studies that treat the LOT-R as a unidimensional measure" (p.437).…”
mentioning
confidence: 99%
“…Research with LOT found systematically two dimensions (Bailey, Eng, Frisch, & Snyder, 2007;Brenes, Rapp, Rejeski, PAIS RIBEIRO, PEDRO, AND MARQUES & Miller, 2002;Chang, D'Zurilla, & Maydeu-Olivares, 1994;Chang & Mcbride-Chang, 1996;Fournier, de Ridder, & Bensing, 1999;Herzberg, Glaesmer, & Hoyer, 2006;Marshall, Wortman, Kusulas, Hervig, & Vickers, 1992;Mroczek, Spiro III, Aldwin, Ozer, & Bossy, 1993;Raikkonen, & Matthews, 2008;Robinson-Whelen, Kim, MacCallum, & KiecoltGlaser,1997;Smith, Pope, Rhodewalt, & Poulton, 1989). Even the creators of the LOT found that it consisted of two factors, namely optimism and pessimism, with factor loadings corresponding to the negatively and the positively worded items (Scheier & Carver, 1985), but they did, however, consider the LOT to be onedimensional for pragmatic reasons, even though they acknowledged the possibility of examining optimism and pessimism scores separately.…”
mentioning
confidence: 99%